Place Marketing and Tourism Development and Its Impact on the City of Cracow - Sebastian BRANKA (Communications of International Proceedings, 2021)
In this paper the author uses the example of the city of Cracow to analyse how certain place marketing activities influence the development of tourism in the city. For this purpose, the notion of place marketing is defined and instruments of place marketing are pointed and exemplified. The Author uses empirical data to illustrate the impact of tourism on the city both in terms of profits from tourism and perception of tourists by the residents and media, the spatial distribution of tourism in the city. The Author focuses on externalities caused by the development of tourism. In the final part of the paper and the conclusions the author posits recommendations on the potential fields of tourism management by the city authorities from the perspective of place marketing.
Keywords: Place marketing; tourism; city development.